2016
DOI: 10.18632/oncotarget.11041
|View full text |Cite
|
Sign up to set email alerts
|

Three new pancreatic cancer susceptibility signals identified on chromosomes 1q32.1, 5p15.33 and 8q24.21

Abstract: Genome-wide association studies (GWAS) have identified common pancreatic cancer susceptibility variants at 13 chromosomal loci in individuals of European descent. To identify new susceptibility variants, we performed imputation based on 1000 Genomes (1000G) Project data and association analysis using 5,107 case and 8,845 control subjects from 27 cohort and case-control studies that participated in the PanScan I-III GWAS. This analysis, in combination with a two-staged replication in an additional 6,076 case an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 74 publications
2
89
0
Order By: Relevance
“…Together these studies identified 16 common low risk pancreatic cancer susceptibility loci that reached the genome-wide significance threshold: 10 −7.3 (i.e. P<5×10 −8 ) (Supplementary Table 1) (2428). …”
Section: Introductionmentioning
confidence: 96%
“…Together these studies identified 16 common low risk pancreatic cancer susceptibility loci that reached the genome-wide significance threshold: 10 −7.3 (i.e. P<5×10 −8 ) (Supplementary Table 1) (2428). …”
Section: Introductionmentioning
confidence: 96%
“…There is no data on differences in pancreatic cancer risk by race/ethnicity in these high-risk syndromes. GWAS studies have identified 16 chromosomal loci with significant associations with pancreatic cancer [42,43]. These studies have included only a modest number of Blacks [44,45]) limiting evaluation of associations in this high-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an imputation analysis of the GWAS data in 5,107 cases and 8,845 controls from PanScan I–III had uncovered three new pancreatic cancer signals on chromosome 1q32.1 ( NR5A2 ), 8q24.21 ( MYC ), and 5p15.33 ( CLPTM1L-TERT ), all of which are independent from previously reported susceptibility variants 107 .…”
Section: Common Low-risk Susceptibility Locimentioning
confidence: 87%
“…To identify common susceptibility variants, five pancreatic cancer GWAS have been conducted by the Pancreatic Cancer Cohort Consortium (PanScan) and the Pancreatic Cancer Case Control Consortium (PanC4) in populations of European ancestry, including PanScan I in 2009 103 , PanScan II in 2010 104 , PanScan III in 2014 105 , PanC4 in 2015 106 and a recent imputation analysis of GWAS data from PanScan I–III 107 . A total of 16 pancreatic cancer susceptibility loci located in 13 genomic regions have been discovered in European populations (Table 2).…”
Section: Common Low-risk Susceptibility Locimentioning
confidence: 99%
See 1 more Smart Citation